The association of urinary plasmin level with renal involvement and disease flare among systemic lupus erythematosus patients - Rasha Fawzy,; Mounir Serag,; Amal Soliman,; Sania Elwia,; Samia Mojahed, (Archives of Rheumatology, 2022)
Objectives: To explore the ability to use urinary level of plasmin as an indicator for renal affection and activity in systemic lupus erythematosus (SLE) patients. Patients and methods: Between April 2020 and October 2020, urine samples from 50 SLE patients (2 males, 48 females; mean age: 35.5±8.1 years; range, 22 to 39 years) and 20 age- and sex-matched healthy controls (2 males, 18 females; mean age: 34.1±6.5 years; range, 27 to 38 years) were collected. The patients were divided into two groups according to the presence or absence of renal manifestations as those with renal disease (n=28) and those without renal disease (n=22). The Systemic Lupus Erythematosus Disease Activity Index (SLEDAI), renal activity (rSLEDAI), and Systemic Lupus International Collaborating Clinics Damage Index (SLICC-DI) scores were calculated. Renal biopsy was performed to patients with active lupus nephritis (LN). The activity index (AI) and Chronicity Index (CI) were scored. Results: There was a highly statistically significant difference in the mean urinary plasmin levels between SLE cases and the control group (88.9±42.6 ng/mL vs. 21.3±26.8 ng/mL, respectively; p<0.001). A significant elevation was observed (p<0.05) in patients with LN (97.9±46.6 ng/mL) than without (42.7±12.7 ng/mL), particularly in patients with active renal involvement (82.9±26.6 ng/mL) than patients with inactive renal disease (63.2±15.5 ng/mL). There were significant positive correlations between the mean urinary plasmin levels and inflammatory markers, SLEDAI, and rSLEDAI scores. Conclusion: Urinary level of plasmin is significantly elevated among SLE cases, particularly in those with active LN. The remarkable association between urinary plasmin level and various activity status implies that urinary plasmin can be used as a beneficial marker to monitor lupus nephritis flare.